METHODS OF FORMING MATHEMATICAL MOBILITY OF FUTURE ENGINEERS IN HIGHER MATHEMATICS CLASSES - Khomyuk, Irina; Kyrylashchuk, Svetlana; Khomyuk, Victor; Bondarenkо Zlata; Klieopa, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Continuous education today is a major feature of modern society. In order to ensure the competitiveness of future professionals who obtain higher education within the walls of the Institutions of Higher Education, the education process should be aimed at ensuring a high level of professional knowledge as well as the formation of graduates' adaptability to changeable modern production. Since for a future engineer knowledge of higher mathematics is the basis for solving complex problems of a production nature, it can be argued that they are part of professional mobility. The implementation of technologies for the formation of professional mobility in higher mathematics has made it possible to note that the readiness to change activities can be considered not only in the context of changing professional activity, but also in the process of students’ educational activity. And this, in turn, made it possible to determine the «mathematical mobility». The purpose of the article is to theoretically substantiate and practically test the methods of forming mathematical mobility of future engineers in higher mathematics classes. The experiment used competency-oriented tasks, test tasks in higher mathematics, built on the basis of Bloom's taxonomy, developed interactive methods for conducting practical classes in the process of studying higher mathematics. The results of the experiment showed the effectiveness of the proposed innovative technologies in the process of fundamental training of future engineers.